2018
DOI: 10.3390/molecules23112808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In Vitro Digestion on Water-in-Oil-in-Water Emulsions Containing Anthocyanins from Grape Skin Powder

Abstract: The effects of in vitro batch digestion on water-in-oil-in-water (W/O/W) double emulsions encapsulated with anthocyanins (ACNs) from grape skin were investigated. The double emulsions exhibited the monomodal distribution (d = 686 ± 25 nm) showing relatively high encapsulation efficiency (87.74 ± 3.12%). After in vitro mouth digestion, the droplet size (d = 771 ± 26 nm) was significantly increased (p < 0.05). The double W1/O/W2 emulsions became a single W1/O emulsion due to proteolysis, which were coalesced tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Shear rate ramps (flow curves) were performed on each emulsion for days 1 to 20. All flow curves showed a decrease in viscosity as a function of shear rate, indicating that all systems had non-Newtonian shear-thinning flow behaviour, consistent with other double emulsion studies [ 16 , 28 , 30 ]. According to McClements, shear-thinning can occur due to altered spatial distribution of particles; non-spherical particle alignment with a flow field; removal of bound solvent molecules; and the deformation of flocs [ 25 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Shear rate ramps (flow curves) were performed on each emulsion for days 1 to 20. All flow curves showed a decrease in viscosity as a function of shear rate, indicating that all systems had non-Newtonian shear-thinning flow behaviour, consistent with other double emulsion studies [ 16 , 28 , 30 ]. According to McClements, shear-thinning can occur due to altered spatial distribution of particles; non-spherical particle alignment with a flow field; removal of bound solvent molecules; and the deformation of flocs [ 25 ].…”
Section: Resultssupporting
confidence: 89%
“…Microencapsulation of bioactive molecules by means of a double emulsion has previously been shown to protect specific molecules (e.g., vitamin B 12 , resveratrol, curcumin) from degradation and/or interference from other components [ 10 ]. Several studies have also shown that inclusion of anthocyanin molecules in the internal aqueous phase of a double emulsion can protect them from changes in pH [ 11 ], temperature [ 12 ], and during simulated mouth and gastric digestion [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to its chemical structure of a dimethyl ether analog of resveratrol, pterostilbene showed a better membrane permeability and metabolic stability, which consequently increases its bioavailability and pharmacokinetic properties [92] . In a recent study, polyphenolic derivatives with increased lipophilicity have shown better cellular absorption, greater antioxidant capacity and greater antiproliferative effect on tumor cells grown in vitro [94] . Also, new procedures to protect polyphenols from digestive degradation have been studied, in order to allow these bioactive compounds to reach their therapeutic targets through food [94] .…”
Section: Discussionmentioning
confidence: 99%
“…Lavelli and Sri Harsha [51] also reported a low EE of 68% in a study where alginate hydrogel was used as an agent to encapsulate phenolic compounds from grape skin. Another study using grape skin extracts, encapsulated in water-in-oilin-water (W/O/W) double emulsions, observed an improved EE of 87.74 ± 3.12% for anthocyanins [52]. The EE depends on a variety of factors, such as the technique used, the solubility and size of the guest molecule relative to the cavity of the host, the concentrations of the host and guest molecules, the binding constant within the guest and host, etc.…”
Section: Encapsulation Efficiencymentioning
confidence: 99%